Spotlight on: Professor Anna Leone - Bridging ancient history and heritage preservation across North Africa (2025)
London: Durham University has issued the following news release: Professor Anna Leone is a leading authority on North African archaeology and heritage protection. Her work is driven by her fascination with ...
Keywords: Archéologie – Djebel Nefousa

In search of the Romans in Jabal Nafusa in surrounding areas - Sjöström, Isabella (Tripolitania in the Roman Empire and Beyond, 2025)
This book provides an up-to-date account of the archaeology, history, economy, urbanism, art, and architecture of the North African region of Tripolitania during antiquity. The essays by international scholars outline current research and the most recent developments in the archaeology of this territory. The strong interdisciplinary character of the texts reflects the expertise of the different authors – from studies of the landscape and urban development, to funerary practices, architecture, military operations and food supply. This timely publication provides a much-needed new assessment of the evolution of this region throughout the Roman and Late Antique period.
Keywords: Archéologie – Djebel Nefousa